KEUNGGULANBERASSOLOK SEBAGAI DAYA TARIK AGROWISATA TANAMAN PANGAN DI KABUPATEN SOLOK, SUMATERA BARAT - Anton Gunarto (JURNAL KEPARIWISATAAN, 2009)
Agrotourism is alternative tourism in which agriculture is the main attraction of tourism activities. Solok rice, well-known for its delicious taste and beautiful farm ground and traditional process, is expected to be developed into agrotourism attraction. This study, therefore, aims to identify the potential, conservation efforts, and how to create an image of Solok rice for agrotourism development. In addition, an agrotourism modeling concept appropriate for agrotourism development in Solok District is discussed. The study found out that Subdistrict of Gunung Talang has the potential to be the center of agrotourism area for Solok rice demfarm. To support this developement, the followings are required: structured technical sectors, organizing the area, human resources developement, appropriate marketing models in order to sell agrotourism product, and appropriate methods and mechamism for funding and its management.